(untitled) - Hornsby, Arthur G (New York, 1996)
This book and diskette provide a unique database compiled from extensive literature searches on pesticide properties in the environment. It presents data on hundreds of pesticides, including: Names (common, commercial, and scientific); Chemical formulas and CAS numbers; Environmental fate properties (water solubility, field half-life, sorption coefficient, vapor pressure, dissociation constants)
Keywords: pesticides,water pollution potential; environmental aspects,handbooks, manuals, etc,handbooks, manuals